Literatur Review Pemberian Jus Wortel dan Relaksasi Napas Dalam Efektif Terhadap Penurunan Dismenorrhea Pada Wanita Usia Subur - Wahyuni Wahyuni; Agnes Montolalu; Hesti Mawarti (POLTEKKES KEMENKES MANADO, 2022)
Background: Dysmenorrhea is pain in the lower abdomen that is felt before, during and even after menstruation. The percentage of the incidence of dysmenorrhea in Indonesia is 55%, but only a few perform examinations in health services. Efforts to reduce dysmenorrhea can be done in two ways, namely pharmacological and non-pharmacological. Pharmacological means can be given analgesic drug therapy. While the non-pharmacological method is one of them by giving carrot juice and deep breathing relaxation. Objective: To compare the effectiveness between consuming carrot juice and deep breathing relaxation on the reduction of dysmenorrhea. Methods: Literature review was conducted critically on the scientific sites Science Direct, PubMed, Elsevier, Garuda, and Google scholar using the keywords dysmenorrhea, carrot juice, and deep breath relaxation. Results: The search results obtained 175 articles but only 15 articles consisting of 9 articles describing carrot juice with dysmenorrhea and 6 articles describing deep breath relaxation with dysmenorrhea. Conclusion: There is an effect of giving carrot juice and relaxation of deep breaths on decreasing the scale of menstrual pain (dysmenorrhea), before, during and even after menstruation.